2021
DOI: 10.13057/biodiv/d220264
|View full text |Cite
|
Sign up to set email alerts
|

Agro-morphological traits and harvest period assessment of winged bean (Psophocarpus tetragonolobus) genotypes for pods production

Abstract: Abstract. Ishthifaiyyah SA, Syukur M, Trikoesoemaningtyas, Maharijaya A. 2021. Agro-morphological traits and harvest period assessment of winged bean (Psophocarpus tetragonolobus) genotypes for pods production. Biodiversitas 22: 1069-1075. Winged bean (Psophocarpus tetragonolobus) is an underutilized crop in Indonesia. Winged bean varieties for pods productions not only must have high productivity and nutrient contents, but also have a long harvest period. This research aimed to evaluate agro-morphological tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
3
4
0
Order By: Relevance
“…The total number of seeds per accession, total seed weight, terminal leaf length, terminal leaf width, pod length, dry pod weight, and number of seeds per pod also exhibited a GCV and PCV. The outcome from the current study was like previous work in winged bean accessions (Afridatul and Syukur 2021;Kant and Nandan 2018;Mohamadali et al 2010;Prasanth et al 2016;Rajeshwar et al 2009). Furthermore, PCV values were observed to be higher than GCV for all the traits evaluated.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The total number of seeds per accession, total seed weight, terminal leaf length, terminal leaf width, pod length, dry pod weight, and number of seeds per pod also exhibited a GCV and PCV. The outcome from the current study was like previous work in winged bean accessions (Afridatul and Syukur 2021;Kant and Nandan 2018;Mohamadali et al 2010;Prasanth et al 2016;Rajeshwar et al 2009). Furthermore, PCV values were observed to be higher than GCV for all the traits evaluated.…”
Section: Discussionsupporting
confidence: 88%
“…Winged bean (Psophocarpus tetragonolobus (L.) DC.,) is a member of the underutilized or orphan legumes in the tropics but with proven ability for vigorous twining habit, Nitrogen fixation capacity and tuberous root system (Eagleton 2020;Vatanparast et al 2016). It grows in the world's most common agro-ecologies (the hot, humid equatorial countries) (Afridatul and Syukur 2021;Lepcha et al 2017). The United States Academy of Science gave the limelight to the crop in a 1975 publication and since then research attention has focused on the crop particularly on its agronomy, nutritional composition, and other aspects of crop improvements but subsequently, research interest dwindled but current evidence showed renewed interest at crop promotion and molecular breeding activities being exploited amongst other interventions (Eagleton 2020;Lepcha et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…At 6 WAP, TVU 14788 (35.97) recorded the highest number of leaves and least mean value was obtained from TVU 14346 (29.49). Results from this study agrees with Sayyidah et al (2021) who emphasised that difference in genotypes could cause variation in the number of leaves formation of winged bean. At 9 WAP, the trend was similar in which TVU 14788 (40.20) had the highest number of leaves and TVU 14346 (33.28) gave the least mean value.…”
Section: Resultssupporting
confidence: 91%
“…It has demonstrated a robust twining habit, nitrogen fixation capability, and the presence of a tuberous root system [1,2]. Thriving in the most prevalent agro-ecologies worldwide, particularly in hot and humid equatorial countries [3,4] this versatile plant holds promise for agricultural cultivation. It comes under Fabaceae with chromosome number 2n = 2x = 18, or 22.…”
Section: Introductionmentioning
confidence: 99%